ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI GENERASI MILENIAL TERHADAP KEPUTUSAN PEMBE LIAN SMARTPHONE - Zusrony Edwin (SMART Management Journal, 2021)
The use of smartphones for the millennial generation will now become a primary need which is the main requirement in supporting various activities, both telecommunications, and entertainment. This study tries to analyze the various factors that influence the millennial generation in making choices in smartphone purchasing decisions with all STEKOM University students as respondents. The number of samples in this study amounted to 100 people with a sampling method using convenience sampling, namely selecting respondents based on the ease of finding or access. Data analysis using multiple linear regression method and processed with the help of SPSS 25. Based on the test results show that price, product quality, and lifestyle have a significant and positive effect on purchasing decisions of smartphones. The variable that is the most dominant and the most influential is the price variable.